A new species of genus Trilocha Moore, [1860] from Great Nicobar Island, India (Lepidoptera, Bombycoidea, Bombycidae) - Singh, Navneet; Ahmad, Jalil; Chandra, Kailash (Zootaxa, 2021)
In this paper, we describe a new bombycid, Trilocha nicobari N. Singh & Ahmad, sp. nov., distributed in Great Nicobar Island. The new species is diagnosed with all its congeners. A checklist and a taxonomic key to the known species of Trilocha is provided.